Nucleosome structure and positioning modulate nucleotide excision repair in the non-transcribed strand of an active gene. - Wellinger, R E (1997)
Nucleotide excision repair (NER) is a major pathway to remove pyrimidine dimers (PDs), a class of DNA lesions generated by ultraviolet light. Since folding of DNA into nucleosomes restricts its accessibility and since transcription and DNA repair require access to DNA, nucleosome structure and positioning as well as the transcriptional state may affect DNA repair. We recently determined the chromatin structure of the yeast URA3 gene at high resolution and found multiple positions of nucleosomes as well as strand- and site-specific variation in DNA accessibility to DNase I (internal protected regions). Here, the same high-resolution primer extension technique was used to investigate NER of PDs in the URA3 gene of a mini-chromosome in vivo. In the non-transcribed strand (NTS), fast repair correlates with PD locations in linker DNA and towards the 5' end of a positioned nucleosome. Slow repair correlates with the internal protected region of the nucleosome. This repair heterogeneity reflects a modulation of NER by positioned nucleosomes in the NTS. NER in the transcribed strand (TS) is fast, less heterogeneous and shows no correlation with chromatin structure. Apparently, transcription-coupled repair overrides chromatin modulation of NER in the TS. Heterogeneity in NER generated by chromatin structure on the NTS may contribute to heterogeneity in mutagenesis.